2020
DOI: 10.1016/j.envsoft.2019.104557
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring through many eyes: Integrating disparate datasets to improve monitoring of the Great Barrier Reef

Abstract: Numerous organisations collect data in the Great Barrier Reef (GBR), but they are rarely analysed together due to different program objectives, methods, and data quality. We developed a weighted spatio-temporal Bayesian model and used it to integrate image-based hard-coral data collected by professional and citizen scientists, who captured and/or classified underwater images. We used the model to predict coral cover across the GBR with estimates of uncertainty; thus filling gaps in space and time where no data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Looking forward, this work comprises a specific network model for each country/region (Table 1) and a more advanced system, accounting for the geographic origin of the data, will facilitate its applications in global monitoring. Furthermore, propagating the classification uncertainty from the machine into statistical analyses will ensure a more robust integration and interpretation of monitoring data (e.g., [41]).…”
Section: Challenges and Further Considerations In Automated Benthic Amentioning
confidence: 99%
“…Looking forward, this work comprises a specific network model for each country/region (Table 1) and a more advanced system, accounting for the geographic origin of the data, will facilitate its applications in global monitoring. Furthermore, propagating the classification uncertainty from the machine into statistical analyses will ensure a more robust integration and interpretation of monitoring data (e.g., [41]).…”
Section: Challenges and Further Considerations In Automated Benthic Amentioning
confidence: 99%
“…Firstly, ecological monitoring data are not always sufficient in coverage or detail to confidently draw conclusions [38]. Reefs host complex benthic communities of diverse algae and invertebrate taxa, and in-water assessments relying on SCUBA can be time-consuming and require expertise for identification.…”
Section: The Challenge: Using Monitoring Data To Understand the Effecmentioning
confidence: 99%
“…In addition, monitoring the GBR is especially challenging because it extends over 346, 000 km 2 and traditional marine surveys are expensive (Nichols & Williams, 2006;Nygård et al, 2016;Roelfsema & Phinn, 2010;Vercelloni et al, 2020). To address these issues, Peterson et al (2020) demonstrated how image-based coral cover data elicited from citizens can be combined with other professional data sources to improve the spatio-temporal data coverage in the GBR and increase the information gained to inform management. This approach was operationalised in the Virtual Reef Diver project using the weighted approach (https://www.virtu alreef.org.au/), without accounting for misclassification bias.…”
Section: Origins Of Coral Reef Imagesmentioning
confidence: 99%
“…Approaches that pool or integrate CS elicited data with those obtained from professional monitoring programmes are gathering momentum (Peterson et al., 2020). This idea revolves around meta‐analysis principles and has been extensively studied in many areas including medicine, social sciences, and the environment (see Claggett et al., 2014; Higgins et al., 2009; Rice et al., 2018), as well as ecological settings (Koricheva et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation